Edward III and the English peerage : royal patronage, social mobility, and political control in fourteenth-century England - Bothwell, James (Boydell Press, 2004)
Patronage was central to medieval kingship, and a crucial facet of royal power. This book, the first in-depth examination of this crucial facet of royal power, offers a detailed analysis of how Edward III, one of the most successful and, to use a modern term, charismatic of medieval English monarchs, used royal favour to create a 'new nobility' and to reward and control the established peerage. Dr Bothwell shows how judicious use of largesse helped to produce domestic stability and encouraged the successful prosecution of foreign wars. Further, the study demonstrates how the nature of royal patronage came to reflect changes in feudalism, land law, finance, and the Church and the consequences of these changes for the more general history of medieval patronage, the evolution of the Lords and Commons, and the state of royal power both at the centre and in the localities. Overall, it is a clear, concise study of how Edward III used patronage to reposition the monarchy after the vicissitudes of his father's reign and a problematic minority. J.S. BOTHWELL is Lecturer in Later Medieval English History, University of Leicester.